2021
DOI: 10.1111/mec.15752
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression during larval caste determination and differentiation in intermediately eusocial bumblebees, and a comparative analysis with advanced eusocial honeybees

Abstract: The queen‐worker caste system of eusocial insects represents a prime example of developmental polyphenism (environmentally‐induced phenotypic polymorphism) and is intrinsic to the evolution of advanced eusociality. However, the comparative molecular basis of larval caste determination and subsequent differentiation in the eusocial Hymenoptera remains poorly known. To address this issue within bees, we profiled caste‐associated gene expression in female larvae of the intermediately eusocial bumblebee Bombus ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 133 publications
0
8
0
Order By: Relevance
“…Studies on lncRNA expression in honey bees have been increasing in recent years, focused mainly on caste determination [ 19 , 31 ], the behavioral transition from nurse to forager [ 25 ], oviposition [ 32 , 33 ], and the response to pathogen infestation [ 20 , 21 , 34 ]. In the current study, RNA-seq was performed to identify the lncRNA and mRNA profiles of honey bees exposed to 0.01 mg/L dinotefuran for 1, 5, and 10 d to assess the potential regulators of honey bee growth and immune responses related to neonicotinoid insecticides.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on lncRNA expression in honey bees have been increasing in recent years, focused mainly on caste determination [ 19 , 31 ], the behavioral transition from nurse to forager [ 25 ], oviposition [ 32 , 33 ], and the response to pathogen infestation [ 20 , 21 , 34 ]. In the current study, RNA-seq was performed to identify the lncRNA and mRNA profiles of honey bees exposed to 0.01 mg/L dinotefuran for 1, 5, and 10 d to assess the potential regulators of honey bee growth and immune responses related to neonicotinoid insecticides.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that queen specialization is under the strict control of the social environment is inconsistent with the traditional view of social insect queens as being intrinsically specialized in egg production (Hölldobler & Wilson, 1990; Wilson, 1971), but rather indicates that their specialization is dependent on social conditions and is more flexible than typically assumed. We argue that it is not sufficient to study caste differentiation (Ashby et al., 2016; Cameron et al., 2013; Collins et al., 2020; Corona et al., 2016; Genzoni et al., 2023; Libbrecht et al., 2011; Libbrecht, Corona, et al., 2013; Libbrecht, Oxley, et al., 2013; Montagna et al., 2015; Mutti et al., 2011; Psalti & Libbrecht, 2020; Schultner et al., 2023; Schwander et al., 2008; Schwander & Keller, 2008; Wheeler et al., 2006) and/or compare adult queens and workers (Bonasio et al., 2012; Chandra et al., 2018; Corona et al., 2007, 2013; Feldmeyer et al., 2014; Grozinger et al., 2007; Kronauer & Libbrecht, 2018; Libbrecht, Oxley, et al., 2013; Patalano et al., 2015) to fully understand division of labour in insect societies. It is necessary to also investigate the transition from pluripotent to specialized queens, as well as the maintenance of the queen specialization.…”
Section: Discussionmentioning
confidence: 97%
“…The many investigations that tackled this question can be separated in three broad categories. First, studies of caste determination and differentiation uncovered critical information on the regulation of alternative developmental trajectories that lead to the production of queens and workers (Ashby et al., 2016; Cameron et al., 2013; Collins et al., 2020; Corona et al., 2016; Genzoni et al., 2023; Libbrecht et al., 2011; Libbrecht, Corona, et al., 2013; Libbrecht, Oxley, et al., 2013; Montagna et al., 2015; Mutti et al., 2011; Psalti & Libbrecht, 2020; Schultner et al., 2023; Schwander et al., 2008; Schwander & Keller, 2008; Wheeler et al., 2006). Second, studies comparing adult queens and workers in mature colonies revealed a suite of caste‐specific phenotypic and molecular differences (Bonasio et al., 2012; Chandra et al., 2018; Corona et al., 2007, 2013; Feldmeyer et al., 2014; Grozinger et al., 2007; Kronauer & Libbrecht, 2018; Libbrecht, Oxley, et al., 2013; Patalano et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A high wing loading is therefore likely to put more constraints on the thoracic flight muscles. Annotations associated with wing loading included Dmrt (doublesex and mab‐3‐related transcription factor), which in social insects may be involved in regulating caste‐specific polyphenism (Collins et al., 2021; Lago et al., 2022). In addition, annotated genes were involved in stabilizing muscle–tendon attachment during flight and wing epithelia (mechanosensitive adaptor protein talin; Klapholz & Brown, 2017; Lemke et al., 2019).…”
Section: Discussionmentioning
confidence: 99%